Directive Illocutionary Acts in Me Before You Movie - Ayu Oktaviani; Dewi Syafitri; Syafrizal Syafrizal (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aims to know the types of directive illocutionary act dominantly used in Me Before You. The researcher used quantitative and qualitative methods to describe and analyze the most dominant illocutionary act in Me Before You. The result showed that there are six types of Illocutionary acts that are used in this movie. There are advising (36%), commanding (24.5%), requesting (22%), admonishing (10%), urging (5%) and ordering (2.5%). In conclusion, the Me Before You movie contained all types of Illocutionary Acts. Keywords: Directive, Illocutionary Act, Movie